Advanced imaging to extend the therapeutic time window of acute ischemic stroke. Issue 1 (1st February 2013) - Fisher, Marc; Albers, Gregory W.
Abstract: Reperfusion therapy for acute stroke has evolved from the initial use of intravenous tissue plasminogen activator (tPA) within 3 hours of symptom onset to more recent guideline‐recommended use up to 4.5 hours. In addition, endovascular therapy is increasingly utilized for stroke treatment and is typically initiated up to 8 hours after onset. Recent studies demonstrate that imaging of the ischemic penumbra with diffusion/perfusion magnetic resonance imaging (MRI) can identify subgroups of patients who are likely to improve following successful reperfusion (Target Mismatch profile) and others who are at increased risk for hemorrhage and poor clinical outcomes (Malignant profile). New data indicate that stent retriever devices provide better recanalization efficacy and clinical outcomes than the previously available mechanical thrombectomy devices. Going forward, we believe that the use of penumbral imaging with validated MRI techniques, as well as the currently less well‐validated computed tomography (CT) perfusion approach, will maximize benefit and reduce the risk of adverse events and poor outcomes when used both early after stroke onset and at later time points. New trials that feature diffusion/perfusion MRI or CT perfusion‐based patient selection for treatment with intravenous tPA and or endovascular therapies versus nonreperfused control groups are planned or in progress. We predict that these trials will confirm the hypothesis that penumbral imaging can enhance patient selection and extend the therapeutic time window for acute ischemic stroke. ANN NEUROL 2013.